Sonic and Photonic Crystals - Lien-Wen Chen; Jia-Yi Yeh (Crystals, 2020)
Sonic/phononic crystals named acoustic/sonic band gap media are the elastic analogues of photonic crystals and have received renewed attention recently in many acoustic applications [...]